Ce-MOF doped Nafion composite proton exchange membrane as well as preparation method and application thereof
By introducing Ce-MOF into the Nafion composite proton exchange membrane, the free radical quencher effect of Ce and the anchoring effect of MOF are used to combine the interaction between amino groups and sulfonic acid groups, the problems of complex preparation, high cost and poor performance of the existing membrane are solved, and efficient proton conduction and electrolyzed hydrogen production are achieved.
Patent Information
- Application Number
- CN202411877952.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing Nafion composite proton exchange membrane has defects in the complex preparation process, high cost, low conductivity and poor chemical durability, and it is difficult to meet the needs of efficient electrolysis of hydrogen production.
By introducing Ce-MOF, Ce is used as a radical quencher to enhance the chemical stability of the membrane and anchor the Ce ion position through the MOF backbone to solve the problem of Ce ion migration, while introducing amino groups and sulfonic acid groups on the Nafion chain to form proton transport channels to improve the proton conductivity.
It has achieved high proton transfer rate, redox capacity and catalytic activity in the temperature range of 25-130°C, while improving the mechanical properties of the membrane and the efficiency of electrolyzing hydrogen production.
Smart Images

Figure CN119685879A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by electrolysis of water using a proton exchange membrane, and in particular to a Ce-MOF-doped Nafion composite proton exchange membrane and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane water electrolysis (PEMWE) is considered a promising green hydrogen production technology due to its high efficiency, high reliability and rapid response. At present, the most widely used proton exchange membrane (PEM) is the Nafion membrane developed by DuPont. The membrane has the characteristics of high proton conductivity and good mechanical stability at room temperature, but it has the disadvantages of complex preparation process, high cost and poor stability.
[0003] Metal organic frameworks (MOFs) have been one of the most attractive porous materials since their introduction. They have excellent characteristics such as adjustable pore size, regular void cages and adjustable surface properties. As a potential new type of proton conductor, they are used to modify and improve existing proton exchange membranes and enhance the proton conductivity and other properties of proton exchange membranes. Among the tetravalent metals that can be used to form M-MOFs (M=Ti, Zr, Hf, Ce, U, Th, etc.), Ce(IV) has a low-space occupied 4f orbital, which can accelerate the charge transfer from ligand to metal, and has the ability to switch between oxidation (IV) and reduction (III) states. It can scavenge free radicals by switching between different valence states, and can be introduced into proton exchange membranes as free radical quenchers to enhance the chemical stability of the membranes.
[0004] CN117603543A discloses a de-MOF / Nafion composite membrane and its preparation method and application. The secondary structural unit of de-MOF has the property of inorganic polyacid, which can be doped into the Nafion membrane as a proton source, and the ability of water storage in the composite membrane is realized by forming a dynamic hydrogen bond network in the Nafion membrane, and then the proton conductivity of the Nafion membrane is improved by efficiently transferring protons through the jumping mechanism. The composite membrane is obtained by immersing the Nafion membrane in the de-MOF dispersion and stirring for two days. It has the problem that MOF is easy to lose, and does not involve the study of water absorption, swelling and oxidation resistance of the composite membrane under different temperature conditions.
[0005] CN117209825A discloses a polymer hybrid proton exchange membrane modified by a metal organic framework functionalized by -PO3H2 / -NH2 acid-base pairs, wherein the proton exchange membrane introduces a metal organic framework (P-MOF-NH2) functionalized by -PO3H2 / -NH2 acid-base pairs to hybridize the polymer, and the porous structure of P-MOF-NH2 and the modification of hydrophilic groups -PO3H2 and -NH2 make P-MOF-NH2 have high water affinity, which can greatly enhance the water retention of the membrane, thereby promoting the proton conduction of the membrane. The conductivity and stability of the composite membrane are both good, but it does not involve resisting free radical attacks to improve the chemical stability of the proton membrane.
[0006] The existing technology has the defects of complex preparation process, low conductivity of Nafion membrane at high temperature and poor chemical durability. Therefore, how to improve the conductivity and chemical durability of Nafion composite proton exchange membrane has become a problem that needs to be solved urgently. Summary of the invention
[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a Ce-MOF-doped Nafion composite proton exchange membrane and its preparation method and use. The Ce-MOF-doped Nafion composite proton exchange membrane of the present invention has a high proton transfer rate and redox ability, and has high catalytic activity and stability within the operating temperature range of 25-130°C.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a Ce-MOF-doped Nafion composite proton exchange membrane, wherein the Ce-MOF-doped Nafion composite proton exchange membrane comprises a Nafion composite proton exchange membrane and Ce-MOF; the metal site in the Ce-MOF is Ce; and the Ce-MOF contains amino groups.
[0010] In order to solve the problem that Nafion membrane is easily attacked by free radicals during use, which leads to membrane degradation, the present invention introduces Ce element and uses Ce as a free radical quencher to effectively remove free radicals. 3+ and Ce 4+ , inhibiting the chemical degradation of polymer chains, is beneficial to improving the durability of proton exchange membranes and enhancing the antioxidant properties of proton exchange membranes.
[0011] On the other hand, considering the disadvantage of easy migration of Ce ions, the present invention uses a MOF skeleton to anchor the position of Ce ions, effectively solving the problem of Ce loss after long-term work, and at the same time introduces amino groups and sulfonic acid groups on the Nafion chain to form a proton transmission channel, thereby ensuring the proton conductivity of the membrane.
[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0013] Preferably, the mass fraction of the Ce-MOF is 1wt%-9wt%, for example, it can be 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt% or 9wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 4wt%-6wt%.
[0014] The present invention further regulates the mass fraction of Ce-MOF to be 1wt%-9wt%, so that the Ce-MOF-doped Nafion composite proton exchange membrane has more excellent conductivity, can significantly improve the Fenton mass loss rate, and the prepared composite proton exchange has higher mechanical properties and exhibits higher electrolysis current in the process of water electrolysis to produce hydrogen. If the mass fraction of Ce-MOF is lower than 1wt%, the -NH2 and -SO3H brought by a small amount of doping will interact with each other, making it difficult to form a continuous hydrogen bond network, increasing the uncertainty of proton transfer, and reducing the conductivity of the Ce-MOF-doped Nafion composite proton exchange membrane; if the mass fraction of Ce-MOF is higher than 9wt%, the Ce-MOF powder inside the composite membrane will be severely agglomerated, destroying the orderly establishment of proton transfer channels in the membrane, increasing defect sites, and causing the conductivity of the Ce-MOF-doped Nafion composite proton exchange membrane to decrease, the brittleness of the composite membrane to increase, and the tensile strength and electrolysis voltage to decrease. The present invention further prefers that the mass fraction of Ce-MOF in the Ce-MOF-doped Nafion composite proton exchange membrane is 4wt%-6wt%, at which time the comprehensive performance is the best.
[0015] Preferably, the Ce-MOF comprises UIO-66.
[0016] The Ce-MOF of the present invention includes UIO-66. Compared with the conventional prior art method of anchoring CeO2 on fibers and nanotubes, the strong bonding effect formed by the coordination between the metal ions and organic ligands of MOF solves the migration problem of Ce ions. The adjustable surface properties of UIO-66 are utilized to ensure the conductivity of the proton exchange membrane through the synergistic effect of the two functional groups of -NH2 and -SO3H loaded.
[0017] In a second aspect, the present invention provides a method for preparing a Ce-MOF-doped Nafion composite proton exchange membrane as described in the first aspect, the preparation method comprising the following steps:
[0018] (1) mixing cerium salt, an organic ligand containing an amino group, water and ethanol, and performing a first reaction to obtain a Ce-MOF containing an amino group;
[0019] (2) mixing the Ce-MOF containing amino groups with the Nafion solution, performing a second reaction, and obtaining a dispersion. The dispersion is cast and annealed to obtain the Ce-MOF-doped Nafion composite proton exchange membrane.
[0020] In the process of preparing the metal organic framework, the present invention uses an organic ligand containing an amino group as an organic ligand, thereby preparing a metal organic framework with an amino group; subsequently, the amino group interacts with the sulfonic acid group on the Nafion chain, which is conducive to forming a proton transmission channel with small steric hindrance, thereby ensuring the proton conductivity of the membrane; the preparation method of the Ce-MOF-doped Nafion composite proton exchange membrane of the present invention has simple process, low cost, mild conditions, and is green and environmentally friendly.
[0021] Preferably, the cerium salt comprises a tetravalent cerium salt.
[0022] Preferably, the tetravalent cerium salt comprises any one or a combination of at least two of ammonium cerium nitrate, cerium acetate or cerium sulfate, wherein typical but non-limiting combinations include a combination of ammonium cerium nitrate and cerium acetate, a combination of cerium acetate and cerium sulfate, a combination of ammonium cerium nitrate and cerium sulfate, and a combination of ammonium cerium nitrate, cerium acetate and cerium sulfate.
[0023] Preferably, the amino-containing organic ligand comprises 2-aminoterephthalic acid.
[0024] Preferably, the molar ratio of the cerium salt to the amino-containing organic ligand is (3-5):(2-8), for example, 3:2, 3.4:3, 3.5:3.2, 4:3, 4.5:5.7, 4:7 or 5:8, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] The present invention further controls the molar ratio of the cerium salt to the amino-containing organic ligand to satisfy (3-5): (2-8), thereby regulating the structure of the Ce-MOF generated by the reaction, making the structure obtained by the reaction more complete and having a suitable pore structure, and at the same time affecting the conductivity and mechanical properties of the prepared Ce-MOF-doped Nafion composite proton exchange membrane. If the molar ratio of the cerium salt or the amino-containing organic ligand is too large or too small, the number of crystal nuclei will be reduced, or even no nuclei will be formed.
[0026] Preferably, acetic acid is added before the first reaction.
[0027] In the present invention, acetic acid can maintain the acid-base environment of the reaction system and promote the formation of the UIO-66 structure. Adding acetic acid is more conducive to forming a uniform solution, ensuring the uniform distribution of metal ions, and inhibiting side reactions, which is conducive to the growth of better and purer crystals.
[0028] Preferably, the volume ratio of acetic acid, water and ethanol is (5-10):(15-30):(30-60), for example, it can be 5:15:30, 5:20:30, 6:15:30, 6:20:40, 7:15:30, 7:20:30, 7:20:35, 7:20:40, 8:25:30, 8:30:30, 8:20:35, 8:20:40, 8:25:40, 8:25:50, 9:25:30, 9:30:30, 9:20:35, 10:20:40, 10:25:40, 10:25:50, 10:25:60 or 10:30:60, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0029] In the present invention, ethanol is used as a medium during the synthesis process to affect the dispersion and assembly of cerium ions and amino-containing organic ligand molecules. The presence of ethanol molecules is conducive to the formation of an ordered structure, thereby affecting the pore structure and specific surface area of MOF.
[0030] Step (1) further includes washing and a first drying after the first reaction.
[0031] Preferably, the specific steps of washing are: washing with water and / or ethanol for 3 to 6 times, for example, 3 times, 4 times, 5 times or 6 times respectively.
[0032] Preferably, the first drying comprises vacuum drying.
[0033] Preferably, the first drying temperature is 60°C-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the first drying time is 12h-24h, for example, it can be 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h or 24h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the method for preparing the Nafion solution comprises: drying the Nafion aqueous alcohol solution to obtain a Nafion resin, and mixing the Nafion resin with a solvent to obtain a Nafion solution.
[0036] Preferably, the Nafion hydroalcoholic solution comprises any one of Nafion D2020 solution, Nafion D1020 solution or Nafion D520 solution, or a combination of at least two thereof, wherein typical but non-limiting combinations include a combination of Nafion D2020 solution and Nafion D1020 solution, a combination of Nafion D1020 solution and Nafion D520 solution, a combination of Nafion D2020 solution and Nafion D520 solution, and a combination of Nafion D2020 solution, Nafion D1020 solution and Nafion D520 solution.
[0037] Preferably, the drying temperature is 60°C-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Preferably, the solvent comprises any one of anhydrous ethanol, isopropanol, N,N-dimethylformamide or N,N-dimethylacetamide, or a combination of at least two thereof, wherein typical but non-limiting combinations include a combination of anhydrous ethanol and isopropanol, a combination of isopropanol and N,N-dimethylformamide, a combination of N,N-dimethylformamide and N,N-dimethylacetamide, a combination of anhydrous ethanol, isopropanol and N,N-dimethylformamide, and a combination of anhydrous ethanol, isopropanol, N,N-dimethylformamide and N,N-dimethylacetamide.
[0039] Preferably, the mass fraction of Nafion resin in the Nafion solution is 5wt%-20wt%, for example, it can be 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0040] Preferably, the temperature of the second reaction in step (2) is 60°C-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, the time of the second reaction in step (2) is 12h-24h, for example, it can be 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h or 24h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] Preferably, step (2) includes performing ultrasonic dispersion for 0.5h-1h after the second reaction, for example, 0.5h, 0.6h, 0.8h or 1h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0043] Preferably, step (2) further includes a second drying step after pouring.
[0044] Preferably, the second drying temperature is 60°C-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] Preferably, the second drying time is 12h-24h, for example, it can be 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h or 24h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] Preferably, the annealing temperature is 100°C-150°C, for example, it can be 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, the annealing time is 2h-12h, for example, it can be 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:
[0049] (1) mixing ammonium cerium nitrate, 2-aminoterephthalic acid, acetic acid, water and ethanol, wherein the molar ratio of the ammonium cerium nitrate to the 2-aminoterephthalic acid is (3-5):(2-8); the volume ratio of the acetic acid, water and ethanol is (5-10):(15-30):(30-60), performing a first reaction, washing with water and / or ethanol for 3 to 6 times respectively, and vacuum drying at 60° C. to 80° C. for 12 h to 24 h to obtain a Ce-MOF containing an amino group;
[0050] (2) drying the Nafion aqueous alcohol solution at 60° C.-80° C. to obtain Nafion resin, mixing the Nafion resin with a solvent, and stirring at 70° C.-80° C. for 12 h-24 h to obtain a Nafion solution with a mass fraction of 5 wt %-20 wt %;
[0051] (3) mixing the amino-containing Ce-MOF of step (1) with the Nafion solution of step (2), performing a second reaction at 60° C.-80° C. for 12 h-24 h, and ultrasonically dispersing for 0.5 h-1 h to obtain a dispersion; pouring the dispersion into a 7.5 cm×7.5 cm glass tank, performing a second drying at 60° C.-80° C. for 12 h-24 h, and annealing at 100° C.-150° C. for 2 h-12 h to obtain the Ce-MOF-doped Nafion composite proton exchange membrane.
[0052] In a third aspect, the present invention provides a use of the Ce-MOF-doped Nafion composite proton exchange membrane as described in the first aspect, wherein the Ce-MOF-doped Nafion composite proton exchange membrane is used for producing hydrogen by electrolysis of water.
[0053] The Ce-MOF-doped Nafion composite proton exchange membrane of the present invention is used for electrolysis of water to produce hydrogen to improve proton conductivity and enhance the chemical stability of the membrane. The simple functionalization feature of MOFs enables it to effectively modify hydrophilic groups and provide active sites for proton transfer. At the same time, the strength of the metal ion and oxygen ion bond and the unique geometric structure greatly preserve the Ce ion content. The Ce-MOF-doped Nafion composite proton exchange membrane improves proton conductivity, thermal stability and chemical and physical durability. These characteristics help to improve the efficiency of electrolysis of water to produce hydrogen and reduce costs. At the same time, it broadens the operating temperature range and service life of the proton exchange membrane, reduces the water absorption rate and swelling rate, and ensures the dimensional stability of the composite membrane.
[0054] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0055] Compared with the prior art, the present invention has at least the following beneficial effects:
[0056] (1) The present invention introduces Ce element and uses Ce as a free radical quencher to effectively remove free radicals, and the reversible redox reaction of Ce 3+ and Ce 4+ , inhibiting the chemical degradation of polymer chains, which is beneficial to improving the durability of proton exchange membranes and enhancing the antioxidant properties of proton exchange membranes. On the other hand, considering the disadvantage of easy migration of Ce ions, the present invention adopts Ce-MOF containing amino groups, anchors the position of Ce ions through the MOF skeleton, effectively solves the problem of Ce loss after long-term work, and introduces amino groups and sulfonic acid groups on the Nafion chain to form a proton transmission channel, ensuring the proton conductivity of the membrane.
[0057] (2) In the process of preparing the metal organic framework, the present invention uses 2-aminoterephthalic acid as an organic ligand to prepare a metal organic framework with an amino group; the amino group subsequently interacts with the sulfonic acid group on the Nafion chain, which is conducive to forming a proton transmission channel with small steric hindrance, thereby ensuring the proton conductivity of the membrane; the preparation method of the Ce-MOF-doped Nafion composite proton exchange membrane of the present invention is simple in process, low in cost, mild in conditions, and green and environmentally friendly.
[0058] (3) The Ce-MOF-doped Nafion composite proton exchange membrane of the present invention is used for electrolysis of water to produce hydrogen to improve proton conductivity and enhance the chemical stability of the membrane. The simple functionalization of MOFs enables it to effectively modify hydrophilic groups and provide active sites for proton transfer. At the same time, the strength of the metal ion and oxygen ion bond and the unique geometric structure greatly preserve the Ce ion content. The Ce-MOF-doped Nafion composite proton exchange membrane improves proton conductivity, thermal stability and chemical and physical durability. These characteristics help to improve the efficiency of electrolysis of water to produce hydrogen and reduce costs. At the same time, it broadens the operating temperature range and service life of the proton exchange membrane, reduces the water absorption rate and swelling rate, and ensures the dimensional stability of the composite membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 is the XRD spectrum of the Ce-MOF containing amino groups prepared in Example 1 of the present invention;
[0060] Figure 2 is the infrared spectrum of the Ce-MOF containing amino groups prepared in Example 1 of the present invention;
[0061] Figure 3 It is a graph showing the change of conductivity of the Nafion composite proton exchange membranes prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 and 2 with temperature;
[0062] Figure 4It is a graph of swelling rate and water absorption rate of Nafion composite proton exchange membranes prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 and 2;
[0063] Figure 5 It is a graph showing the variation of the Fenton mass loss rate of the Nafion composite proton exchange membrane prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 and 2;
[0064] Figure 6 It is a comparison chart of the stretching rates of Nafion composite proton exchange membranes prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 and 2;
[0065] Figure 7 It is a polarization curve spectrum of hydrogen production by electrolysis of water using Nafion composite proton exchange membrane prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 and 2;
[0066] Figure 8 It is the XRD spectrum of Ce-MOF prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0067] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0068] In the following examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the field; unless otherwise specified, the experimental methods and technical means used were conventional methods and means in the field.
[0069] Example 1
[0070] This embodiment provides a Ce-MOF-doped Nafion composite proton exchange membrane, wherein the Ce-MOF-doped Nafion composite proton exchange membrane comprises a Nafion composite proton exchange membrane and Ce-MOF; the metal site in the Ce-MOF is Ce, the Ce-MOF contains an amino group, and the mass fraction of the Ce-MOF is 5wt%;
[0071] The preparation method of the Ce-MOF-doped Nafion composite proton exchange membrane provided in this embodiment comprises the following steps:
[0072] (1) mixing ammonium cerium nitrate, 2-aminoterephthalic acid, acetic acid, water and ethanol for a first reaction, wherein the molar ratio of ammonium cerium nitrate to 2-aminoterephthalic acid is 3.4 mmol:3 mmol; the volume ratio of acetic acid, water and ethanol is 6 mL:16 mL:40 mL, and solid-liquid separation is performed to obtain a brown solid, and the brown solid is washed with water and ethanol for 3 times respectively, and vacuum dried at 70° C. for 12 h to obtain a Ce-MOF containing an amino group;
[0073] (2) drying a Nafion D2020 solution at 70° C. for 12 h to obtain a Nafion resin, mixing the Nafion resin with N,N-dimethylformamide, and stirring at 70° C. for 12 h to obtain a Nafion solution with a mass fraction of 5 wt%;
[0074] (3) Mixing the amino-containing Ce-MOF of step (1) and the Nafion solution of step (2) for a second reaction at 70° C. for 12 h, ultrasonically dispersing for 0.5 h to obtain a dispersion, pouring the dispersion into a 7.5 cm×7.5 cm glass tank, second drying at 80° C. for 12 h, annealing at 130° C. for 2 h, cooling to room temperature, and peeling the composite membrane from the glass tank to obtain the Nafion composite proton exchange membrane with a Ce-MOF doping amount of 5 wt%.
[0075] The XRD pattern of the prepared Ce-MOF is shown in Figure 1 As shown, from Figure 1 It can be seen that the structure of MOF in Ce-MOF conforms to the expected crystal structure of UIO-66. In the figure, 7.13° corresponds to the (111) crystal plane and 8.19° corresponds to the (002) crystal plane.
[0076] The infrared image of the prepared Ce-MOF is as follows Figure 2 As shown, from Figure 2 It can be seen that Ce-MOF contains amino groups.
[0077] Example 2
[0078] This embodiment provides a Ce-MOF-doped Nafion composite proton exchange membrane, wherein the Ce-MOF-doped Nafion composite proton exchange membrane comprises a Nafion composite proton exchange membrane and Ce-MOF; the metal site in the Ce-MOF is Ce, the Ce-MOF contains an amino group, and the mass fraction of the Ce-MOF is 1wt%;
[0079] The preparation method of the Ce-MOF-doped Nafion composite proton exchange membrane provided in this embodiment comprises the following steps:
[0080] (1) mixing ammonium cerium nitrate, 2-aminoterephthalic acid, acetic acid, water and ethanol for a first reaction, wherein the molar ratio of ammonium cerium nitrate to 2-aminoterephthalic acid is 4 mmol:3.5 mmol; the volume ratio of acetic acid, water and ethanol is 10 mL:16 mL:45 mL, and a brown solid is obtained after stirring and solid-liquid separation. The brown solid is washed with water and ethanol for 3 times respectively, and vacuum dried at 60° C. for 20 h to obtain a Ce-MOF containing an amino group;
[0081] (2) drying the Nafion D1020 solution at 80° C. for 12 h to obtain Nafion resin, mixing the Nafion resin with anhydrous ethanol, and stirring at 80° C. for 12 h to obtain a Nafion solution with a mass fraction of 10 wt%;
[0082] (3) Mixing the amino-containing Ce-MOF of step (1) and the Nafion solution of step (2) for a second reaction at 60° C. for 24 h, ultrasonically dispersing for 0.5 h to obtain a dispersion, pouring the dispersion into a 7.5 cm×7.5 cm glass tank, second drying at 80° C. for 12 h, annealing at 100° C. for 12 h, cooling to room temperature, and peeling the composite membrane from the glass tank to obtain the Nafion composite proton exchange membrane with a Ce-MOF doping amount of 1 wt%.
[0083] Example 3
[0084] This embodiment provides a Ce-MOF-doped Nafion composite proton exchange membrane, wherein the Ce-MOF-doped Nafion composite proton exchange membrane comprises a Nafion composite proton exchange membrane and Ce-MOF; the metal site in the Ce-MOF is Ce, the Ce-MOF contains an amino group, and the mass fraction of the Ce-MOF is 3wt%;
[0085] The preparation method of the Ce-MOF-doped Nafion composite proton exchange membrane provided in this embodiment comprises the following steps:
[0086] (1) mixing ammonium cerium nitrate, 2-aminoterephthalic acid, acetic acid, water and ethanol for a first reaction, wherein the molar ratio of ammonium cerium nitrate to 2-aminoterephthalic acid is 4 mmol:4.5 mmol; the volume ratio of acetic acid, water and ethanol is 6 mL:16 mL:40 mL, and solid-liquid separation is performed to obtain a brown solid, and the brown solid is washed with water and ethanol for 3 times respectively, and vacuum dried at 70° C. for 12 h to obtain a Ce-MOF containing an amino group;
[0087] (2) drying the Nafion D520 solution at 70° C. for 12 h to obtain Nafion resin, mixing the Nafion resin with isopropanol, and stirring at 70° C. for 12 h to obtain a Nafion solution with a mass fraction of 10 wt%;
[0088] (3) Mixing the amino-containing Ce-MOF of step (1) and the Nafion solution of step (2) for a second reaction at 70° C. for 12 h, ultrasonically dispersing for 0.5 h to obtain a dispersion, pouring the dispersion into a 7.5 cm×7.5 cm glass tank, second drying at 80° C. for 12 h, annealing at 150° C. for 2 h, cooling to room temperature, and peeling the composite membrane from the glass tank to obtain the Nafion composite proton exchange membrane with a Ce-MOF doping amount of 3 wt%.
[0089] Example 4
[0090] This embodiment provides a Ce-MOF-doped Nafion composite proton exchange membrane, wherein the Ce-MOF-doped Nafion composite proton exchange membrane comprises a Nafion composite proton exchange membrane and Ce-MOF; the metal site in the Ce-MOF is Ce, the Ce-MOF contains an amino group, and the mass fraction of the Ce-MOF is 7wt%;
[0091] The preparation method of the Ce-MOF-doped Nafion composite proton exchange membrane provided in this embodiment comprises the following steps:
[0092] (1) mixing ammonium cerium nitrate, 2-aminoterephthalic acid, acetic acid, water and ethanol for a first reaction, wherein the molar ratio of ammonium cerium nitrate to 2-aminoterephthalic acid is 3 mmol:2 mmol; the volume ratio of acetic acid, water and ethanol is 6 mL:20 mL:45 mL, and solid-liquid separation is performed to obtain a brown solid, and the brown solid is washed with water and ethanol for 5 times respectively, and vacuum dried at 70° C. for 12 h to obtain a Ce-MOF containing an amino group;
[0093] (2) drying a Nafion D2020 solution at 70° C. for 12 h to obtain a Nafion resin, mixing the Nafion resin with N,N-dimethylacetamide, and stirring at 70° C. for 12 h to obtain a Nafion solution with a mass fraction of 5 wt%;
[0094] (3) mixing the amino-containing Ce-MOF of step (1) and the Nafion solution of step (2), reacting at 70° C. for 12 h, and ultrasonically dispersing for 0.5 h to obtain a dispersion, casting the dispersion into a 7.5 cm×7.5 cm glass tank, drying at 80° C. for 12 h, annealing at 120° C. for 2 h, cooling to room temperature, and peeling the composite membrane from the glass tank to obtain the Nafion composite proton exchange membrane with a Ce-MOF doping amount of 7 wt%.
[0095] Example 5
[0096] This embodiment provides a Ce-MOF-doped Nafion composite proton exchange membrane, wherein the Ce-MOF-doped Nafion composite proton exchange membrane comprises a Nafion composite proton exchange membrane and Ce-MOF; the metal site in the Ce-MOF is Ce, the Ce-MOF contains an amino group, and the mass fraction of the Ce-MOF is 9wt%;
[0097] The preparation method of the Ce-MOF-doped Nafion composite proton exchange membrane provided in this embodiment comprises the following steps:
[0098] (1) mixing ammonium cerium nitrate, 2-aminoterephthalic acid, acetic acid, water and ethanol for a first reaction, wherein the molar ratio of ammonium cerium nitrate to 2-aminoterephthalic acid is 5 mmol:4.5 mmol; the volume ratio of acetic acid, water and ethanol is 10 mL:25 mL:50 mL, and solid-liquid separation is performed to obtain a brown solid, and the brown solid is washed with water and ethanol for 6 times respectively, and vacuum dried at 70° C. for 12 h to obtain a Ce-MOF containing an amino group;
[0099] (2) drying a Nafion D2020 solution at 70° C. for 12 h to obtain a Nafion resin, mixing the Nafion resin with N,N-dimethylformamide, and stirring at 70° C. for 12 h to obtain a Nafion solution with a mass fraction of 5 wt%;
[0100] (3) mixing the amino-containing Ce-MOF of step (1) and the Nafion solution of step (2) for a second reaction at 70° C. for 12 h, ultrasonically dispersing for 0.5 h to obtain a dispersion, casting the dispersion into a 7.5 cm×7.5 cm glass tank, second drying at 80° C. for 12 h, annealing at 130° C. for 2 h, cooling to room temperature, and peeling the composite membrane from the glass tank to obtain the Nafion composite proton exchange membrane with a Ce-MOF doping amount of 9 wt%.
[0101] Example 6
[0102] This embodiment provides a Ce-MOF-doped Nafion composite proton exchange membrane, which is different from Embodiment 1 only in that the mass fraction of the Ce-MOF is 0.5 wt %.
[0103] Example 7
[0104] This embodiment provides a Ce-MOF-doped Nafion composite proton exchange membrane, which is different from Embodiment 1 only in that the mass fraction of the Ce-MOF is 10 wt %.
[0105] Example 8
[0106] This embodiment provides a Ce-MOF-doped Nafion composite proton exchange membrane, which is different from Embodiment 1 only in that, when preparing the Ce-MOF-doped Nafion composite proton exchange membrane, the molar ratio of the ammonium cerium nitrate to 2-aminoterephthalic acid is 1 mmol:3 mmol.
[0107] Example 9
[0108] This embodiment provides a Ce-MOF-doped Nafion composite proton exchange membrane, which is different from Embodiment 1 only in that, when preparing the Ce-MOF-doped Nafion composite proton exchange membrane, the molar ratio of the ammonium cerium nitrate to 2-aminoterephthalic acid is 6 mmol:1 mmol.
[0109] Example 10
[0110] This embodiment provides a Ce-MOF-doped Nafion composite proton exchange membrane, which is different from Embodiment 1 only in that, when preparing the Ce-MOF-doped Nafion composite proton exchange membrane, acetic acid is not added in step (1).
[0111] Comparative Example 1
[0112] This comparative example provides a Nafion composite proton exchange membrane, which is different from Example 1 only in that, when preparing the Nafion composite proton exchange membrane, step (1) is not performed and no Ce-MOF containing amino groups is added in step (3).
[0113] Comparative Example 2
[0114] This comparative example provides a CeO2-doped Nafion composite proton exchange membrane, which is different from Example 1 only in that, when preparing the CeO2-doped Nafion composite proton exchange membrane, step (1) is not performed and the Ce-MOF in step (3) is replaced by an equal mass of CeO2.
[0115] Comparative Example 3
[0116] This comparative example provides a Nafion composite proton exchange membrane, which is different from Example 1 only in that, when preparing the Nafion composite proton exchange membrane, the 2-aminoterephthalic acid in step (1) is replaced by an equimolar amount of 2,2'-bipyridine-4,4'-dicarboxylic acid.
[0117] The obtained Ce-MOF was subjected to XRD test, and the results are as follows Figure 8 As shown in the figure, it can be seen that the MOF crystal form is not UIO-66 and the structure was not successfully synthesized.
[0118] Application Example 1-Application Example 9
[0119] The Ce-MOF-doped Nafion composite proton exchange membranes prepared in Examples 1 to 9 were subjected to water electrolysis experiments, and the specific operations were as follows: CCM (catalyst coating membrane method): an ultrasonic sprayer was used to spray cathode and anode catalyst slurries on both sides of the Nafion composite proton exchange membrane to prepare a catalyst layer. The catalyst slurry includes anode (IrO2) or cathode (60% Pt / C) catalyst, deionized water, D520 Nafion ionomer and IPA. The performance of the membrane electrodes of Application Examples 1 to Application Examples 9 was tested under constant current conditions at 80°C. Before testing the electrolysis performance, all membrane electrodes were activated for 0.5h at a certain constant current density. The current density in the range of 1.3V to 2.0V was measured using an electrochemical workstation (Gamry 3000).
[0120] The current density of hydrogen production by water electrolysis is shown in Table 1.
[0121] Comparative Application Example 1-Comparative Application Example 3
[0122] The Nafion composite proton exchange membranes prepared in Comparative Examples 1 to 3 were respectively subjected to water electrolysis experiments. The experimental methods were consistent with those of Application Examples 1 to 9. The current density of hydrogen production by water electrolysis is shown in Table 1.
[0123] Test method: The proton exchange membranes prepared in the above examples and comparative examples were tested for conductivity, water absorption, swelling rate and mechanical strength. The test results are shown in Table 1 below.
[0124] The test method of conductivity is: using electrochemical impedance spectrometer (EIS) CHI 660E (Shanghai Chenhua Instrument Co., Ltd.) to measure the proton conductivity of the composite proton exchange membrane. Before the test, the composite proton exchange membrane was activated at 80°C, and the steps were as follows: 1) heating with 3% H2O2 for 1 hour to remove organic impurities, and then washing with deionized water; 2) heating with 0.5MH2SO4 (aq) for 1 hour to make the active sites of the polymer be H +Completely replace, then rinse with deionized water; 3) Soak in deionized water for 1h to fully remove excess H2SO4. The sample is cut into 10mm×30mm rectangular strips. 10 measuring points are selected to measure the thickness and average D value of the film. In the frequency range of 0.1Hz to 1MHz, the surface resistance R (Ω) of the sample at different temperatures and full humidity is measured to obtain the proton conductivity σ (S / cm), which can be obtained from formula 1:
[0125]
[0126] L (cm) is the distance between the two electrodes (here the distance is 1 cm), S (cm 2 ) is the cross-sectional area of the composite film tape (the product of the width and thickness of the composite film).
[0127] The test method for water absorption is as follows: each film is activated with 0.5MH2SO4 (aq) at 60°C for 24 hours, rinsed with deionized water, and then dried in an oven at 80°C for 24 hours until the mass is constant. The initial mass W1 is recorded. The film is then placed in a water environment, heated to the test temperature for 24 hours to balance, the surface water of the sample is quickly removed, and the test mass W2 is recorded. The experimental results are calculated according to formula 2:
[0128]
[0129] The test method for swelling rate is the same as the test method for water absorption rate. The recorded mass changes W1 and W2 are replaced by area changes A1 and A2. The experimental results are calculated according to formula 3:
[0130]
[0131] The test method of mechanical strength is as follows: the mechanical properties of the film are tested using an electronic universal testing machine. During the test, the sample is cut into 15mm×45mm rectangular strips and measured at a test speed of 50mm / min at room temperature.
[0132] The Fenton mass loss rate test method is: 20ppmFe 2+ (0.02g ferrous sulfate) was added to 100ml H2O2 at 3wt% to prepare Fenton's reagent. Initially, the sample was dried at 80°C for 24 hours and the initial mass W1 was recorded. Afterwards, a 2cm×4cm proton exchange membrane was immersed in Fenton's reagent at 80°C. The sample was taken out every 24 hours, rinsed with deionized water, and dried again in a vacuum oven at 80°C for 24 hours. The weight W2 of the sample was recorded and the Fenton's reagent was replaced. The experimental results after 120h Fenton test were calculated according to formula 4:
[0133]
[0134] The conductivity of the prepared Nafion composite proton exchange membrane changes with temperature as shown in Figure 3 As shown, from Figure 3 It can be seen that Example 1 measured the highest conductivity of 0.22 S / cm at 80° C. and 100% RH. Compared with Comparative Examples 1 and 2, its proton conductivity performance is greatly improved.
[0135] The swelling rate and water absorption rate of the prepared Nafion composite proton exchange membrane are shown in Figure 4 As shown, from Figure 4 It can be seen that after doping with Ce-MOF, the water absorption and swelling rates of the composite membranes of Examples 1-5 are reduced, and their dimensional stability is improved to a certain extent, among which the water absorption and swelling rate of Example 1 are the smallest, which are 10.78% and 9.54% respectively.
[0136] The Fenton mass loss rate spectrum of the prepared Nafion composite proton exchange membrane is as follows: Figure 5 As shown, from Figure 5 It can be seen that after 120h of Fenton test, Example 1 retained the most residual mass of 97.16%, and the introduction of Ce-MOF effectively improved the oxidation resistance of the composite membrane.
[0137] The comparison chart of the elongation rate of the prepared Nafion composite proton exchange membrane is as follows: Figure 6 As shown, from Figure 6 It can be seen that the interaction between -NH2 and -SO3H functional groups also helps to form a dense structure in the membrane, thereby enhancing the mechanical properties of the composite membrane. Example 1 shows a maximum tensile strength of 19.501 MPa.
[0138] The polarization curve of the prepared Nafion composite proton exchange membrane for water electrolysis and hydrogen production is shown in Figure 7 As shown, from Figure 7 It can be seen that in the process of hydrogen production by electrolysis of water, the in-plane proton conductivity of Example 1 is the best, showing 2.63A / cm 2 high current density.
[0139] Table 1
[0140]
[0141] The test results show that:
[0142] (1) It can be seen from Examples 1 to 5 that the present invention introduces the Ce element and uses Ce as a free radical quencher to effectively remove free radicals, and the reversible redox reaction of Ce 3+ and Ce 4+, inhibiting the chemical degradation of polymer chains, which is beneficial to improving the durability of the proton exchange membrane and enhancing the antioxidant properties of the proton exchange membrane. The prepared Ce-MOF-doped Nafion composite proton exchange membrane was applied to the electrolysis of water to produce hydrogen. A continuous hydrogen bond network was constructed inside the membrane, showing a high current density. Among them, Example 1 with the best comprehensive performance had an electrical conductivity of 0.22S / cm at 80°C and 100% RH, and a maximum tensile strength of 19.501MPa. After 120h of Fenton test, Example 1 still retained 97.16% of the mass residual rate. Compared with Comparative Example 1, it has the lowest water absorption and swelling rate and the largest current density of 2.63A / cm 2 .
[0143] (2) By comparing Example 1 with Example 6-Example 7, it can be seen that the present invention further adjusts the mass fraction of Ce-MOF to 1wt%-9wt%, so that the Ce-MOF-doped Nafion composite proton exchange membrane has a more excellent conductivity, can significantly improve the Fenton mass loss rate, and the prepared composite proton exchange has higher mechanical properties. The -NH2 and -SO3H brought by a small amount of doping interact with each other, making it difficult to form a continuous hydrogen bond network, increasing the uncertainty of proton transmission, and reducing the conductivity of the Ce-MOF-doped Nafion composite proton exchange membrane; if the mass fraction of Ce-MOF is higher than 9wt%, the Ce-MOF powder inside the composite membrane will be severely agglomerated, destroying the orderly establishment of the proton transmission channel in the membrane, increasing the defect sites, resulting in a decrease in the conductivity of the Ce-MOF-doped Nafion composite proton exchange membrane, an increase in the brittleness of the composite membrane, and a deterioration in the tensile strength.
[0144] (3) By comparing Example 1 with Example 8-Example 9, it can be seen that the present invention further controls the molar ratio of cerium salt to amino-containing organic ligand to satisfy (3-5): (2-8), thereby regulating the structure of Ce-MOF generated by the reaction, making the structure obtained by the reaction more complete and having a suitable pore structure, and at the same time affecting the conductivity and mechanical properties of the prepared Ce-MOF-doped Nafion composite proton exchange membrane. If the molar ratio of cerium salt or amino-containing organic ligand is too large or too small, it will lead to the inability to form a stable UIO-66 crystal form and structural collapse.
[0145] (4) By comparing Example 1 with Example 10, it can be seen that the addition of acetic acid in the present invention can maintain the acid-base environment of the reaction system and promote the formation of the UIO-66 structure. The addition of acetic acid is more conducive to forming a uniform solution, ensuring the uniform distribution of metal ions and inhibiting side reactions, which is conducive to the growth of better and purer crystals.
[0146] (5) It can be seen from Example 1 and Comparative Examples 1-2 that the present invention introduces Ce element and uses Ce as a free radical quencher to effectively remove free radicals, and the reversible redox reaction of Ce 3+ and Ce 4+ , inhibiting the chemical degradation of polymer chains, which is beneficial to improving the durability of the proton exchange membrane and the antioxidant performance of the proton exchange membrane. At the same time, the interaction between the -NH2 and -SO3H groups is used to form a continuous hydrogen bond network in the membrane, thereby improving the proton transfer efficiency. When Ce-MOF is not doped or CeO2 is introduced, the conductivity of the proton exchange membrane and the performance of hydrogen production by electrolysis of water will deteriorate, and the technical effects of the present invention cannot be achieved.
[0147] (6) It can be seen from Example 1 and Comparative Example 3 that the present invention uses 2-aminoterephthalic acid as an organic ligand to prepare a metal organic framework with a Ce-UIO-66-NH2 structure. If other organic ligands are used, a metal organic framework with a Ce-UIO-66-NH2 structure cannot be prepared, and its efficiency of producing hydrogen by electrolysis of water will also be greatly reduced.
[0148] In summary, the present invention introduces Ce element and uses Ce as a free radical quencher to effectively remove free radicals, and the reversible redox reaction of Ce 3+ and Ce 4+ , inhibiting the chemical degradation of polymer chains, which is beneficial to improving the durability of proton exchange membranes and enhancing the antioxidant properties of proton exchange membranes. On the other hand, considering the disadvantage of easy migration of Ce ions, the present invention adopts the Ce-UIO-66 structure, anchors the Ce ion position through the MOF skeleton, effectively solves the problem of Ce loss after long-term work, and introduces amino groups and sulfonic acid groups on the Nafion chain to form a proton transmission channel, ensuring the proton conductivity of the membrane and significantly improving the current density during water electrolysis to produce hydrogen.
[0149] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A Ce-MOF-doped Nafion composite proton exchange membrane, characterized in that: The Ce-MOF-doped Nafion composite proton exchange membrane comprises a Nafion composite proton exchange membrane and Ce-MOF; The metal site in the Ce-MOF is Ce; The Ce-MOF contains amino groups.
2. The Ce-MOF-doped Nafion composite proton exchange membrane according to claim 1, characterized in that: The mass fraction of the Ce-MOF is 1wt%-9wt%, preferably 4wt%-6wt%; Preferably, the Ce-MOF comprises UIO-66.
3. A method for preparing a Ce-MOF-doped Nafion composite proton exchange membrane as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) mixing cerium salt, an organic ligand containing an amino group, water and ethanol, and performing a first reaction to obtain a Ce-MOF containing an amino group; (2) mixing the Ce-MOF containing amino groups with the Nafion solution, performing a second reaction, and obtaining a dispersion. The dispersion is cast and annealed to obtain the Ce-MOF-doped Nafion composite proton exchange membrane.
4. The preparation method according to claim 3, characterized in that: The cerium salt includes a tetravalent cerium salt; Preferably, the tetravalent cerium salt comprises ammonium cerium nitrate; Preferably, the amino-containing organic ligand comprises 2-aminoterephthalic acid; Preferably, the molar ratio of the cerium salt to the amino-containing organic ligand is (3-5):(2-8); Preferably, the first reaction further comprises adding acetic acid; Preferably, the volume ratio of water to ethanol is (15-30):(30-60); Preferably, the volume ratio of acetic acid, water and ethanol is (5-10):(15-30):(30-60).
5. The preparation method according to claim 3 or 4, characterized in that: Step (1) further comprises washing and a first drying after the first reaction; Preferably, the specific steps of washing are: washing with water and / or ethanol for 3 to 6 times respectively; Preferably, the first drying is vacuum drying; Preferably, the first drying temperature is 60°C-80°C; Preferably, the first drying time is 12h-24h.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The preparation method of the Nafion solution comprises: drying the Nafion aqueous alcohol solution to obtain a Nafion resin, and mixing the Nafion resin with a solvent to obtain a Nafion solution; The Nafion hydroalcohol solution includes any one of Nafion D2020 solution, Nafion D1020 solution or Nafion D520 solution or a combination of at least two thereof; Preferably, the drying temperature is 60°C-80°C.
7. The preparation method according to claim 6, characterized in that: The solvent includes any one of anhydrous ethanol, isopropanol, N,N-dimethylformamide or N,N-dimethylacetamide or a combination of at least two thereof; Preferably, the mass fraction of Nafion resin in the Nafion solution is 5wt%-20wt%.
8. The preparation method according to any one of claims 3 to 7, characterized in that: Step (2) The temperature of the second reaction is 60°C-80°C; Preferably, the time of the second reaction in step (2) is 12h-24h; Preferably, step (2) comprises performing ultrasonic dispersion for 0.5 h to 1 h after the second reaction.
9. The preparation method according to any one of claims 3 to 8, characterized in that: Step (2) further includes a second drying after the pouring; Preferably, the second drying temperature is 60°C-80°C; Preferably, the second drying time is 12h-24h; Preferably, the annealing temperature is 100°C-150°C; Preferably, the annealing time is 2h-12h.
10. A use of the Ce-MOF-doped Nafion composite proton exchange membrane as claimed in claim 1 or 2, characterized in that: The Ce-MOF-doped Nafion composite proton exchange membrane is used for producing hydrogen by electrolyzing water.
Citation Information
Patent Citations
Preparation method of proton exchange membrane blended by perfluorinated sulfonic acid resin and Ce-MOF
CN114373971A
Composite perfluorosulfonic acid proton exchange membrane as well as preparation method and application thereof
CN116826124A